The role of pre-recruitment processes in the maintenance of a barnacle (Chthamalus challengeri Hoek) patch on an intertidal pebble shore in Japan - APOLINÁRIO,M. (1999)
To understand the role of pre-recruitment processes (supply of larvae and recruitment) in the maintenance of an intertidal barnacle (Chthamalus challengeri Hoek) patch, the availability of cyprid larvae and the recruitment on natural pebble substrata was monitored on the Magarisaki pebble shore (Amakusa, Kyushu, Japan) during 1995 and 1996. Also, a hypothesis that predation and/or bulldozing by mobile intertidal mollusks during the post-recruitment period could be an important factor in mortality of these barnacles was tested. The collapse of the adult population and the consequent disappearance of the patch were observed by the middle of 1995. The larval availability was low (@ 6 cyprid larvae/100 l), as was the recruitment (@ 30 recruits/25 cm²). The recruits experienced high mortality, preventing them becoming adults able to maintain the patch. In 1996, a similar pattern of availability of the cyprid larvae, and even lower recruitment occurring only at the upper intertidal level was observed. A mobile mollusks exclusion experiment failed to detect any significant differences among the treatments, supporting the null hypothesis that the observed pattern of distribution was not caused by predation by mobile mollusks. There is my suggestion that the low availability of larvae and the low level of recruitment caused the non-maintenance of the patch.